The General Factor of Self-Control and Cost Consideration: A Critical Test of the General Theory of Crime - Vaughan, Tyler J. (Crime & delinquency, 2019)
The general theory of crime proposes that the components that make up self-control increase crime by "affecting the calculation of the consequences of one's acts" (i.e., cost consideration). Despite receiving empirical attention, little is known about the validity of this aspect of the theory because a general factor of self-control has not been empirically linked to cost consideration. As recent research supports the existence of a general factor, this study examines the impact of a general factor and specific factors on cost consideration and offending intentions. Results support the existence of a general factor, which has a large direct effect on offending intentions, but only a small indirect effect, in contrast to the theory's predictions. Implications for the theory and future research are presented.